Stategic ANALISA KOMPETENSI SUMBER DAYA MANUSIA DALAM PENGEMBANGAN PRODUKSI UMKM BUBUTAN DIDESA BATOKAN KECAMATAN KASIMAN KABUPATEN BOJONEGORO - Retno Muslinawati; Dados Susilowati; Edy Suhartono; Moh. Azus Shony Azar; Azhari Azhari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The formulation of the problem of this research are: a. What is the Description of the Implementation of HR Competencies in the Production Development Strategy of Small and Medium Enterprises for Lathe Crafts in Kasiman District in Bojonegoro Regency. B. What is the appropriate marketing strategy for MSMEs for Lathe Crafts in Kasiman Bojonegoro District. The objectives of this research are: a. To find out how the description of the implementation of HR competencies in the Production Development Strategy of MSMEs for Lathe Crafts in Kasiman Bojonegoro District. To find out how the appropriate marketing strategy for MSMEs for Lathe Crafts in Kasiman Bojonegoro District. This study uses a SWOT analysis with the following results: 1. Overview of the Implementation of Human Resource Competencies in the Production Development Strategy of MSMEs for Lathe Crafts in Kasiman Bojonegoro District are: 1. SO (Strength Opportunities) Strategy / Strengths and Opportunities (Strategic Location, Complete Business Permit , Raw Materials, Employees/Labour, Product Availability, Product Type, Product Quality) 2. WO Strategy (Weakness Opportunities) / Weaknesses and Opportunities (Improved simple management, Promotion Enhancement, Addition of Marketing HR, Set sales targets, Market Share and Process marketing). 3. ST Strategy (Strength Streats) / Strengths and Threats (Product Design, Product Quality, Product Competitors. 4. WT Strategy (Weakness Streats) / Weaknesses and Threats (Determining effective and efficient marketing strategies, Maximizing the role of marketing, promotion and management management) production) 2. Marketing strategies that are suitable for the Small and Medium Enterprises of Lathe Crafts, Kasiman Bojonegoro District, namely: Promotion, Price and Product.